2008
DOI: 10.1007/978-3-540-79309-0_9
|View full text |Cite
|
Sign up to set email alerts
|

On the Approximability of Combinatorial Exchange Problems

Abstract: In a combinatorial exchange a set of indivisible products is traded between buyers and sellers which are interested in bundles (multi-sets of products). Although combinatorial exchanges are a natural and important generalization of combinatorial auctions, their approximability has not been studied. We investigate the computational approximability of several social goals and show that the problems of surplus maximization and volume maximization (subject to positive surplus) are inapproximable even with free dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Our focus in this paper was not computational complexity, but it turns out that all of our mechanisms run in polynomial time, except the mechanism for combinatorial exchanges (see [12,4] for computational issues in combinatorial exchanges). Developing a polynomial time mechanism for the latter setting seems hard as in particular it implies a solution to the notorious problem of developing truthful polynomial time algorithm for combinatorial auctions with subadditive (and submodular) bidders (see, e.g., [7], [9], and [8]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our focus in this paper was not computational complexity, but it turns out that all of our mechanisms run in polynomial time, except the mechanism for combinatorial exchanges (see [12,4] for computational issues in combinatorial exchanges). Developing a polynomial time mechanism for the latter setting seems hard as in particular it implies a solution to the notorious problem of developing truthful polynomial time algorithm for combinatorial auctions with subadditive (and submodular) bidders (see, e.g., [7], [9], and [8]).…”
Section: Discussionmentioning
confidence: 99%
“…Theorem: There exists a truthful, individually rational, weakly budget balanced, randomized mechanism that provides an 8H t -approximation to the optimal welfare if all valuations are subadditive 4 . The only distributional knowledge that the mechanism uses is the median value of the distribution of the endowment of each player.…”
Section: Combinatorial Exchangesmentioning
confidence: 99%
“…This property ensures that the exchange does not run at a loss. Also Babaioff et al [15] have shown that the problems of surplus maximization or volume maximization (EFF) in Shantanu [16], [19] have shown that in a combinatorial exchange with multiple buyers and sellers, even with discriminatory pricing, competitive equilibrium may not exist. Therefore we can only achieve competitive equilibrium under special conditions.…”
Section: Introductionmentioning
confidence: 98%
“…This property ensures that the exchange does not run at a loss. Also Babaioff et al [13] have shown that the problems of surplus maximization or volume maximization (EFF) in combinatorial exchanges are inapproximable even with free disposal.…”
Section: Introductionmentioning
confidence: 99%